A bi-attribute user equilibrium model considering travellers' regret aversion. Issue 2 (29th November 2019) - Ye, Shunqiang; Ma, Shoufeng; Jia, Ning
Abstract : Extensive empirical evidence indicates that travellers consider a number of qualities (e.g. travel time, monetary cost, and reliability) when deciding between alternative routes. This study focused on monetary cost and travel time and reviewed two traditional user equilibrium models that incorporate both factors: the VOT-based generalised cost user equilibrium (GCUE) and the bi-objective user equilibrium (BUE). Several properties and assumptions of these models are highlighted that may not be realistic. The present paper develops a bi-attribute regret-minimisation user equilibrium (BRminUE) model, in which travellers aim to minimise their regret rather than maximizing their utility in their travel choices. The relationships between GCUE, BRminUE, and BUE were investigated and a simple example verifies the proved properties. The BRminUE model is a special case of the BUE model; however, it is more general than the GCUE model. Numerical analyses on a four-node tolled network indicate the performance of the proposed model.